ANTANGAN DAN PELUANG PEMBELAJARAN MATEMATIKA - Rangkuti, Ahmad Nizar (IAIN PADANGSIDIMPUAN, 2014)
The development of mathematics learning in Indonesia is very alarming. One contributing factor is the lack of realization of the approach or learning strategies used during the learning process. The new paradigm of education is now more emphasis on students as human beings who have the potential to learn and grow. Therefore, it is necessary to apply a variety of learning approaches that are relevant to the learning of mathematics. Learning approach is intended contextual approach, open ended approach, problem-solving approach, and the approach of realistic mathematics education. The fourth approach uses a realistic problem as a starting base of learning so that students are expected to find and reconstruct mathematical concepts or formal mathematical knowledge. Furthermore, students are given the opportunity to apply mathematical concepts to solve everyday problems or problems in other fields. It is necessary for the mathematical concepts for students awoke